Analisis Viabilitas Isolat Bakteri Penambat Nitrogen Azotobacter 33 pada Bahan Pembawa dan Suhu Penyimpanan yang Berbeda - Ismiani, Sri; Wilujeng, Elly Daru Ika (Agropross : National Conference Proceedings of Agriculture, 2023)
Azotobacter is a microorganism that enhances nitrogen availability for plants and has the potential to be used as a biofertilizer. Assessing the viability of microorganisms within a biofertilizer is crucial in determining its quality. The carrier medium and storage temperature influence the viability of Azotobacter bacteria. Therefore, this research aims to identify the most suitable carrier medium and storage temperature to promote the growth of Azotobacter as a biofertilizer before its field application. The study was conducted at the Soil and Environmental Biotechnology Laboratory, Faculty of Agriculture, Bogor Agricultural University. The viability of Azotobacter was tested using Zeolite and Molasses as carrier media, and stored at temperatures of 4°C and 27°C. The parameters observed were the bacterial population count on the 14th day and the 28th day after inoculation. The results showed that the Azotobacter viability analysis using Zeolite as the carrier medium, storage at 4°C resulted in a population count of 3.7 × 106 CFU/ml, in comparison stored at 27°C resulted in an increased population count of 5.3 × 107 CFU/ml on the 28th day after inoculation. On the other hand, the Azotobacter viability analysis using Molasses as the carrier medium, storage at 4°C the bacterial population count reached 8.5 × 108, and storage at 27°C resulted in a bacterial population count of 7.9 × 106 on the 28th day after inoculation. It can be concluded that both of carriers have a good ability. The viability of Azotobacter is better in Molasses as the carrier medium, with storage at 4°C and the viability of Azotobacter is optimal in Zeolite as the carrier medium, with storage at 27°C, maintaining a stable population density without a decrease in the population count.